Flow cytometry (FCM) analysis of endometrial hyperplasia and carcinoma - Kysela, B; Siracký, J; Redecha, M; Bárdos, A (Neoplasma, 1990)
In a series of 52 biopsy specimens (31 endometrial carcinomas, 10 atypical endometrial hyperplasias, and 11 cases of normal endometrium), DNA ploidy and S-phase cell fraction were estimated in paraffin-embedded material. DNA aneuploidy was detected in 2 of the 10 atypical endometrial hyperplasias and 7 of the 31 endometrial carcinomas. The majority of aneuploidy was found to be connected with the loss of tumor differentiation. No ploidy disturbances were found in normal endometrium. The S-phase cell fraction value of normal endometrium was significantly lower when compared with that of endometrial carcinoma. The broad variation in S-phase cell fraction values of the endometrial carcinomas and atypical endometrial hyperplasias was in contrast with the low variability of S-phase cell values of normal endometrium. Very low incidence of aneuploidy in the group of well differentiated endometrial carcinomas (Grade I) enables the suggestion that the presence of aneuploidy predicts a more aggressive disease and that the detection of an aneuploid stemline in atypical endometrial hyperplasia may already indicate the neoplastic transformation.
Keywords: nádorová transformace buněk; hyperplazie endometria; Male; retrospektivní studie; Cell Transformation, Neoplastic; ploidie; mužské pohlaví; Flow Cytometry; průtoková cytometrie; lidé; ženské pohlaví; Humans; Endometrial Hyperplasia; S fáze; Uterine Neoplasms; S Phase; DNA; nádory dělohy; Retrospective Studies; Female; Ploidies